(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The study of medicinal plants, identifying their properties, and investigating their applications in traditional medicine is one of the pressing issues of our time. This article scientifically substantiates the botanical classification, distribution areas, chemical composition, unique medicinal properties, and uses in traditional medicine of Melissa officinalis - the medicinal lemon balm plant.